2015
DOI: 10.1108/jcp-10-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychopathy factors in reactive aggression within a sample of prisoners

Abstract: Purpose -The main objective of this paper is to examine the role of four psychopathy factors (Interpersonal Manipulation, Callous Affect, Erratic Lifestyle, and Antisocial Behaviour) and the length of incarceration in reactive aggression. The predictive effect of dissatisfaction with peer relations, childhood experiences of violence, and criminal friends on reactive forms of aggressive acts is also explored.Design/methodology/approach -One hundred and twenty nine (N = 129) male prisoners incarcerated in Starga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…change by recognising what they want, establishing a goal, and deciding on an appropriate course of action to bring them closer to the desired object (Blumer, 1966 Debowska, Boduszek, Kola, & Hyland, 2014;Debowska, Mattison, & Boduszek, in press;Debowska & Zeyrek Rios, 2015;Dhingra, Boduszek, Palmer, & Shevlin, 2015), future research should include the interpersonal and affective dimensions of psychopathy as separate components.…”
Section: Personality Moderatorsmentioning
confidence: 99%
“…change by recognising what they want, establishing a goal, and deciding on an appropriate course of action to bring them closer to the desired object (Blumer, 1966 Debowska, Boduszek, Kola, & Hyland, 2014;Debowska, Mattison, & Boduszek, in press;Debowska & Zeyrek Rios, 2015;Dhingra, Boduszek, Palmer, & Shevlin, 2015), future research should include the interpersonal and affective dimensions of psychopathy as separate components.…”
Section: Personality Moderatorsmentioning
confidence: 99%
“…Based on previous research findings by Boduszek et al (2016), it may also be suggested that those more skilled at interpersonal manipulation, will be more likely to adapt to social norms provided by prison settings and develop a criminal identity. Even though the researchers considered interpersonal (e.g., grandiosity, deceitfulness, and superficial charm) and affective (e.g., low empathy, lack of remorse, emotional shallowness, and a failure to accept personal responsibility) features of psychopathy as a single dimension, other empirical studies demonstrated that those traits correlate differently with external variables, such as reactive aggression, rape myth acceptance, as well as self-injurious thoughts and behavior (e.g., Debowska, Boduszek, Kola, & Hyland, 2014;Debowska, Mattison, & Boduszek, 2015;Debowska & Zeyrek Rios, 2015;Dhingra, Boduszek, Palmer, & Shevlin, 2015). Accordingly, in order to test the hypothesis that interpersonal manipulation and callous affect may be significantly related to the formation of criminal identity, future research in the area of CSI should include interpersonal and affective dimensions of psychopathy as separate components.…”
mentioning
confidence: 99%